Defining a turnover index for the correlation of biomaterial degradation and cell based extracellular matrix synthesis using fluorescent tagging techniques. (November 2016) - Bardsley, Katie; Wimpenny, Ian; Wechsler, Roni; Shachaf, Yonatan; Yang, Ying; El Haj, Alicia J.
Graphical abstract: Abstract: Non-destructive protocols which can define a biomaterial's degradation and its associated ability to support proliferation and/or promote extracellular matrix deposition will be an essential in vitro tool. In this study we investigate fluorescently tagged biomaterials, with varying rates of degradation and their ability to support cell proliferation and osteogenic differentiation. Changes in fluorescence of the biomaterials and the release of fluorescent soluble by-products were confirmed as accurate methods to quantify degradation. It was demonstrated that increasing rates of the selected biomaterials' degradation led to a decrease in cell proliferation and concurrently an increase in osteogenic matrix production. A novel turnover index (TI), which directly describes the effect of degradation of a biomaterial on cell behaviour, was calculated. Lower TIs for proliferation and high TIs for osteogenic marker production were observed on faster degrading biomaterials, indicating that these biomaterials supported an upregulation of osteogenic markers. This TI was further validated using an ex vivo chick femur model, where the faster degrading biomaterial, fibrin, led to an increased TI for mineralisation within an epiphyseal defect. This in vitro tool, TI, for monitoring the effect of biomaterial degradation on extracellular matrix production may well act as predictor of the selected biomaterials' performance during in vivo studies. Statement of Significance: This paper outlines a novel metric, Turnover Index (TI), which can be utilised in tissue-engineering for the comparison of a range of biomaterials. The metric sets out to define the relationship between the rate of degradation of biomaterials with the rate of cell proliferation and ECM synthesis, ultimately allowing us to tailor material for set clinical requirements. We have discovered some novel comparative findings that cells cultured on biomaterials with increased rates of degradation have lower rates of proliferation but alternatively have a greater production of osteogenic markers compared to materials which degrade slower. By making comparisons in a rigorous manner, we can begin to define a useful matrix for materials which ultimately may aid for clinical selection.